2015
DOI: 10.1371/journal.pone.0141139
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Heparanase Expression Distinguishes Differentiated Thyroid Carcinoma from Benign Neoplasms

Abstract: IntroductionThe search for a specific marker that could help to distinguish between differentiated thyroid carcinoma and benign lesions remains elusive in clinical practice. Heparanase (HPSE) is an endo-beta-glucoronidase implicated in the process of tumor invasion, and the heparanase-2 (HPSE2) modulates HPSE activity. The aim of this study was to evaluate the role of heparanases in the development and differential diagnosis of follicular pattern thyroid lesions.MethodsHPSE and HPSE2 expression by qRT-PCR, imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
1
17
1
Order By: Relevance
“…Several of the 15 non-CGC genes identified have evidence for cancer roles: ANKRD18A in lung cancer 31 , DDX3X and PBRM1 in various cancers 32 , HPSE2 in thyroid carcinoma 33 , MYO5B in gastric cancer 34 . These findings suggest that ExInAtor precision may be better than implied by the analysis of CGC genes alone.…”
Section: Resultsmentioning
confidence: 99%
“…Several of the 15 non-CGC genes identified have evidence for cancer roles: ANKRD18A in lung cancer 31 , DDX3X and PBRM1 in various cancers 32 , HPSE2 in thyroid carcinoma 33 , MYO5B in gastric cancer 34 . These findings suggest that ExInAtor precision may be better than implied by the analysis of CGC genes alone.…”
Section: Resultsmentioning
confidence: 99%
“…Several of the 15 non-CGC genes identified have evidence for cancer roles: ANKRD18A in lung cancer (30), DDX3X and PBRM1 in various cancers (31), HPSE2 in thyroid carcinoma (32), MYO5B in gastric cancer (33). These findings suggest that ExInAtor precision may be better than implied by the analysis of CGC genes alone.…”
Section: Resultsmentioning
confidence: 99%
“…A study of thyroid carcinoma found that the expression of HPSE2 was increased and tumors showed a typical combination of positive labeling for neoplastic cells and negative immunostaining in colloid [8].…”
Section: Introductionmentioning
confidence: 99%